Pemodelan Kurva Pembebanan Transformator Distribusi Berdasarkan Variasi Penetrasi PLTS Atap - Galuh Prawestri Citra Handani; Rahman Azis Prasojo; Nurfi Fuad Al Azah; Salman Alfarisi; Anang Dasa Novfowan; Afidah Zuroida; Rahma Nur Amalia; Rhezal Agung Ananto; Arinalhaq Fatachul Aziiz (Elposys: Jurnal Sistem Kelistrikan, 2025)
Transformers are considered important equipment in the power distribution system. Determining the state of the distribution network loading curve a network model to analyze the impact of the rooftop PV system penetration level. The assumption of penetration is 10% - 100% and based on the amount of transformer power according to the nameplate, which is 160 kVA. The transformer that used is GTT BB1215, which is one of the distribution transformers in the PT PLN (Persero) UP3 South Surabaya. The loading curve modeling uses DIgSILENT PowerFactory 2021 software with the Quasi-Dynamic Simulation feature. Based on the average loading curve of GTT BB1215 for 14 days, there is a fluctuation, starting at 00.00 a.m - 06.00 a.m the load will decrease, the load will increase again at 06.00 a.m – 07.00 p.m, and the peak load at 06.00 p.m - 07.00 p.m with a current of 140 A (96 kW) or 60% of the transformer capacity load. The lowest load occurs at 06.00 a.m with a current of 94 A (65 kW) or 40% of the transformer capacity load. At a penetration level of 10% - 40%, the transformer load decreases significantly. However, when the penetration level exceeds 40%, there is a reverse power flow from the rooftop PV system to the transformer. This condition make the current to continue flowing even though the load on the transformer has reached 0, because the current represents the power flow from the rooftop PV system to the network, not from the customer load.